PENGARUH KINERJA PENANGANAN DAN KUALITAS PELAYANAN BAGASI TERHADAP KEPUASAN PENUMPANG DI MASKAPAI CITILINK RUTE MALANG – JAKARTA - Faiz Albana; Dinarintan Melinda Firdausy (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of handling performance and service quality and determine the attributes of handling performance and service quality on the Citilink Airlines Malang - Jakarta route at Abdurrachman Salech Airport Malang that need to be developed. This research was conducted for one month, using the dimensions of passenger satisfaction, namely professionalism, service responsiveness, service availability, overall satisfaction, comfort. The sample of this research is Citilink airline passengers. The sample in this study used purposive sampling method. Data was collected by using questionnaires and literature studies. The research method uses a quantitative research design in the form of a survey with Classical Assumption Test, Multiple Regression Analysis and Hypothesis Testing. The results of this study indicate that the data is normally distributed with a significance level of 0.282 or greater than 0.05, and indicates that there is a unidirectional relationship between the independent variable and the dependent variable. It can be concluded that Citilink airline passengers at Abdurrachman Saleh Airport Malang are satisfied with the handling performance and service quality provided with a value (69.6%). Each variable dimension can be developed to be able to improve the handling performance and quality of baggage services in this study.